Evaluation of the morphometric variation of frontal sinus in cone-beam computed tomography (CBCT) of paranasal sinus - Kosar Shakeri; Farida Abesi; sina haghanifar; Soraya Khafri (Babol University of Medical Sciences, 2020)
Introduction: The frontal sinus is the most variable part of the paranasal sinuses in terms of symmetry, anatomical features and degree of development. The aim of this study was to assess the morphometric changes of the frontal sinus in cone-beam computed tomography (CBCT) images. Materials & Methods: In this cross-sectional study, 200 CBCT images were examined for anatomical variations such as the presence of frontal sinus, sinus symmetry, lateral frontal sinus extension (LFSE) to orbital roof, scalloping, septum and type of septum. Moreover, Crista Galli (CG) was divided into three equal segments of anterior, middle and posterior in order to have a precise criterion for determining the location of the frontal recess in coronal plane. The data were analyzed using ANOVA with T-test and Chi-square at significant level of P<0.05. Results: Of 200 cases, 113 and 87 ones were male and female with the mean age of 18‒88 years. The results showed that frontal sinus was bilateral in all cases and symmetric in 113(57%) cases. The LFSE to orbital roof had a significant relationship with gender, so that at the external one-third, the LFSE was less frequent in women than men (P <0.001). The most frequent location of the frontal recess was in the posterior one-third of CG (85 (43%)) with significant difference (P=0.012). Conclusion: In this study, frontal sinuses were rather symmetric, and the use of the anatomical CG marker in multiplanar (MPR) images was not feasible method for rapid detection of the frontal recess location in coronal plane.